Synthesis of Heterodimetallic Iridium–Palladium Complexes Containing Two Axes of Chirality: Study of Sequential Catalytic Properties. Issue 27 (22nd July 2013) - Sabater, Sara; Mata, Jose A.; Peris, Eduardo
Abstract: The reaction of [Cp*Cl2 Ir(triazolium‐ylidene)]BF4 (Cp* = pentamethylcyclopentadienyl) with chiral orthometalated palladium dimers results in facile bridge splitting to afford heterodimetallic Ir–Pd* complexes. The structural characteristics of these complexes show the presence of different isomers as a consequence of hindered rotation about the M–Ccarbene bond (M = Ir/Pd). The heterodimetallic complexes contain two axes of chirality related to each metal. The crystal structure of one heterodimetallic iridium–palladium complex derived from the chiral N, N ‐dimethylbenzylamine ligand is described and contains two of the rotamers. The Ir/Pd* complexes have been tested in a sequence of two catalytic reactions, which implies the isomerization and asymmetric hydrophosphination of 1, 3‐diphenylpropargyl alcohol. All the catalysts show high activity in the overall reaction process and excellent regioselectivity, although the enantioselectivities were low. Abstract : The synthesis of iridium/palladium complexes based on the triazolium‐diylidene ligand with a chiral chelate C–N ligand is described. The heterodimetallic Ir–Pd* complexes contain two axes of chirality related to each metal. The Ir/Pd* complexes are active in a sequence of two catalytic reactions, thus implying the isomerization and asymmetric hydrophosphination of 1, 3‐diphenylpropargyl alcohol.